El desarrollo de la velocidad de aceleración mediante el entrenamiento de fuerza en la selección femenina de baloncesto U16 de Loja, 2023-2024. - Herrera Piedra, Franklin Alejandro (2024)
This curricular integration work was developed with the objective of enhancing acceleration speed through strength training in the Loja U16 women's basketball team. A quantitative approach was used, with a quasi-experimental and correlational design; supported by the following methods: scientific, deductive, historical, analytical-synthetic and statistical. For the diagnostic, physical tests were used on the total population of 10 athletes. According to the results obtained on the physical diagnostic tests, it is evident that the athletes in acceleration speed travel 30 meters in an average of 4.75s, in terms of strength and power in squat jump they have an average of 23.98cm., while in the counter movement jumps an average of 25.48cm in height. These results give us pause to take into account these aspects to improve. Based on these results, a strength training plan was designed and applied. It was structured in 10 weeks with a frequency of twice a week in which sports, training activities were carried out. Following this, the same physical tests were applied, in which improvement was evident in the aspects mentioned above. It is concluded that, after the application of the training plan, the athletes decreased an average of 0.22s when traveling the 30m. In the squat jump they increased an average of 2.77cm in the jump height and in the countermovement jump they increased on average 3.38cm in relation to the initial height, demonstrating that acceleration speed can be improved through strength training because the greater strength athletes have, the greater their ability to move with speed the mass, reaching high speed in less time. Keywords: Speed-strength, sports training, physical capacity, sports performance.